Selected Writings on Race and Difference - Hall, Stuart, 1932-2014 (Book collections on Project MUSE., 2021)
"Stuart Hall famously argued that "race is the modality through which class is lived." This collection demonstrates the remarkable range in which a committed thinker constantly sharpened his understanding of contemporary challenges, and sought to articulate problems and opportunities across space and struggles. In a variety of formats, long and short, lecture and essay, scholarly and popular, Hall shows readers not what to think but rather how and why particular approaches might offer usable insights and models for further thought and action"--